Short Film Animation As Media For Teaching Writing Descriptive Text - Dona Nur Faizah; Dian Novita (International Consortium of Education and Culture Research Studies, 2021)
This research is to know the effects of the use of short film animation as media for teaching writing descriptive text for 7thgrade students at Junior High School. The method that used in this study was Quasi-Experimental, which are conducted an experimental class and control class. Based on the results of statistical calculations, the average score in the experimental class the pre-test value is lower than the post-test. Meanwhile, in the control class the average pre-test and post-test results were still as low. The t-test results showed that the tv value was higher than the table (3.80> 1,999) with 62 degrees of freedom and a significance level of 5%. That is, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. So, the use of animated short films gives effect in writing descriptive text.